Enhancing post-disaster tourism marketing communication in Aceh Jaya Regency - Husna, Asmaul; Fahrimal, Yuhdi (Jurnal Kajian Komunikasi, 2024)
Background: Aceh Jaya Regency is currently deeply committed to developing regional tourism as part of the community’s economic recovery following the 2004 tsunami disaster. The Aceh Jaya government has established five tourism villages and identified ten flagship tourism destinations, which are supported by Aceh Jaya Regent Regulation No. 10/2019 on Halal Tourism. Marketing communication is not only useful in connecting tourism businesses with consumers in the post-disaster tourism industry but also essential for emphasizing the differentiation of tourism products and providing added value to potential tourists. Purpose: This research is urgent because it provides an in-depth analysis of post-disaster tourism marketing communication management in Aceh Jaya Regency using the SOSTAC approach. Methods: This research used qualitative methods, with data gathered through interviews, focus group discussions, and field observations. Moreover, data analysis employed thematic analysis to categorize certain themes and obtain analytical generalizations. Result: The research showed that the Aceh Jaya government has implemented a post-disaster tourism management process that includes various aspects, such as identifying tourism potential, empowering local communities in the tourism sector through partnership programs, developing supporting infrastructure, and promoting tourism. This is done because the local government is fully aware that sustainable tourism development will have a positive impact on the economic growth and welfare of the people of Aceh Jaya. Implications: The findings of this study suggest that adopting the SOSTAC approach in future post-disaster tourism marketing communication strategies, supported by policy, can have a multiplier effect on the economic growth of the community.